A new episode of increased urban income inequality in China - Quheng Deng; Björn Gustafsson (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Chapter from: 'Rising Inequality in China: Challenge to a Harmonious Society', edited by Shi Li, Hiroshi Sato and Terry Sicular.
Keywords: 330; Einkommensverteilung; Soziale Ungleichheit; Ballungsraum; China